Morphological and Morphometric Analysis of Orocraniofacial Bones for Estimative Identification Gender - Sari, Wulan Purnama; Soedarsono, Nurtami; Puspitawati, Ria (Newinera Publisher, 2024)
Identification of sex estimation is the first step in the identification process and is one of the priority parameters in the forensic identification process. Identification is made when the condition of the body is unrecognizable due to natural disasters, transport accidents, bomb explosions, ethnic studies and crime investigations, where only a few parts of the body are already incomplete and limited information are available. In forensic odontology, morphological and morphometric analysis of the orocraniofacial bone is an important component that can help in the process of identifying sex estimation because it has different shapes and sizes in each individual and population. This article will discuss morphological and morphometric analysis of several parameters of the orocraniofacial bone, as well as the advantages and limitations of both methods.